Recycling residues from the pulp and paper industries in the civil construction - Zanella, Bruno Pavanelli [UNESP]; de Barros Trannin, Isabel Cristina [UNESP] (My University, 2015)
This study aimed to evaluate the potential use of the dregs-grits compound in the civil construction goods generated by the pulp and the paper industries which uses the Kraft process. The use of this compound in construction materials can be an economical and environmentally viable alternative, but it must be evaluated to ensure that products maintain their quality and meet all regulatory and industrial standards. Thus, after drying, grinding, screening, and chemical characterization, tests were conducted to evaluate the potential of this compound as a substitute for the fine aggregate in a mixed mortar lining. The possible influence of the addition of the dregs-grits compound on the mechanical properties of the mortar tests were evaluated by using compressive strength and tensile strength. The results showed that this compound can be used to produce mixed mortar lining, replacing its mass in up to 20% of sand medium-fine fraction. Although the use of all the fraction medium-fine of the compound dregs-grits monthly generated by the pulp and paper industries, it is necessary to build 952 houses in 90.25 m2, without loss in application of the mixed mortar lining. The social and the environmental benefits by reducing the extraction of sand from the riverbeds and the proper disposal of these wastes would be immeasurable.
Keywords: Coating materials; Dregs; Environmental management; Grits; Industrial wastes